2013
DOI: 10.4236/aim.2013.36066
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Methicillin Resistant Staphylococcus aureus in Burn Patients Admitted to Burn Unit, Dhaka Medical

Abstract: Staphylococcus aureus infection remains an increasing problem for higher morbidity and mortality in burn patients. We sought to determine the frequency of methicillin-resistant S. aureus (MRSA) in burn wound patients and study their drug resistance genes. Samples were collected (August 2010 to October 2011) from burn unit of Dhaka Medical College Hospital (DMCH), Bangladesh. MRSA was identified by conventional culture based methods. S. aureus was confirmed in 44.44% burn wound samples and 22.5% of the isolates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 27 publications
1
1
1
Order By: Relevance
“…In the present study 89.62% samples yielded growth out of 212 wound swabs. Among 21 isolated S.aureus 33.33% were identified as MRSA by both phenotypic and molecular method, which correlates with previous reports from other regions of Bangladesh 4,8 , Pakistan 6 , and USA 15 . However, some studies have reported much higher rates of 56 to 68% 5,16 .…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In the present study 89.62% samples yielded growth out of 212 wound swabs. Among 21 isolated S.aureus 33.33% were identified as MRSA by both phenotypic and molecular method, which correlates with previous reports from other regions of Bangladesh 4,8 , Pakistan 6 , and USA 15 . However, some studies have reported much higher rates of 56 to 68% 5,16 .…”
Section: Discussionsupporting
confidence: 87%
“…In Bangladesh, the isolation rates of methicillinresistant Staphylococcus aureus in hospitals at different cities were reported as 32-62%, which is a high incidence comparable to the United States and European countries 4 . Different studies showed that MRSA was 56.7% in India 5 , 36.1% in Pakistan 6 , and 34.1% & 22.5% in Bangladesh 7,8 . In 2004, Centers for Disease Control and prevention (CDC) reported that MRSA was responsible for more than 50% of all health care associated Staphylococcus aureus infections within the United States 8 .…”
Section: Introductionmentioning
confidence: 97%
“…A study conducted by Jiang et al on burn samples for five years revealed that out of 259 S. aureus isolates, 239 (92.28%) were MRSA, which is higher than our finding. Also, in Bangladesh, Australia, and China, the rates of MRSA were much lower than our obtained results (27)(28)(29). In MRSA isolates in this research, the highest antibiotic resistance was to penicillin (100%) and gentamicin (81.4%), and the highest sensitivity was observed to linezolid (97.7%) and chloramphenicol (83.7%).…”
Section: Discussioncontrasting
confidence: 68%